Detection of pathogenic bacteria in pigeon faecal samples - Chan, Wen Jun (2023)
Pigeons flock in public area especially dining area due to food availability. Pigeon droppings are found in abundance at Block C cafeteria of Universiti Tunku Abdul Rahman (UTAR) Kampar campus, which can lead to health issues due to the presence of pathogenic bacteria such as Campylobacter jejuni, C. coli, Chlamydia psittaci, C. avium, Enterococcus spp., Escherichia coli, Salmonella spp., Shigella spp., and Staphylococcus aureus that can lead to certain diseases such as campylobacteriosis, psittacosis and salmonellosis. Therefore, this project aims to detect the possible pathogenic bacteria in pigeon faecal samples at UTAR Kampar campus Block C Cafeteria. Furthermore, to study the bacterial diversity and lastly raise the awareness of UTAR community towards the potential health risks caused by pigeon faeces. Culture independent methods were used in this project. Genomic DNA was extracted from pigeon faecal sample that collected from Block C cafeteria, followed by amplification of 16S rRNA gene using polymerase chain reaction (PCR) method. The 16S rRNA gene with approximately band size 1.5 kb was cloned into pTG19-T cloning vector. The plasmids were then transformed into TOP10 E. coli competent cells using heat-shock transformation method and plated on Luria Bertani (LB) agar containing proper concentration of Ampicillin antibiotic for screening and selection process. Then, colony PCR was conducted on positive transformants to verify the presence of inserted 16S rRNA gene and select the positive clones. Plasmid extraction was done for the twelve positive clones and 16S rRNA gene PCR were done to verify the presence of 16S rRNA gene in the plasmid. DNA sequencing was done for ten plasmid samples and analysis were conducted using BLASTn. Results from the BLASTn showed six Lactobacillus crispatus, one Lactobacillus ingluviei, one Ligilactobacillus salivarius, one Candidatus Mycoplasma liparidae and one uncultured bacterium. Among the identified bacterial species, all of them are non-pathogenic. Larger sample size is to be included and more robust method such as next-generation sequencing could be performed to enhance the screening efficiency.